Giải các phương trình sau:
a) x^2 – 4x + 4 = 25
b) (5 – 2x)^2 – 16 = 0
c) (x – 3)^3 – (x – 3)(x^2 + 3x + 9) + 9(x + 1)^2 = 15
giải các phương trình sau:
a.3(x-2)-10=5(2x + 1)
b.3x + 2=8 -2(x-7)
c.2x-(2+5x)= 4(x + 3)
d.5-(x +8)=3x + 3(x-9)
e.3x - 18 + x= 12-(5x + 3)
Bài 2: Giải các phương trình sau:
a. (3x + 2)(x2 – 1) = (9x2 – 4)(x + 1)
b. x(x + 3)(x – 3) – 5(x + 2)(x2 – 2x + 4) = 0
c. x(x + 3)(x – 3) + 5(x – 3) = 0
d. (3x – 1)(x2 + 2) = (3x – 1)(7x – 10)
Bài 2: Giải các phương trình sau:
a. (3x + 2)(x2 – 1) = (9x2 – 4)(x + 1)
b. x(x + 3)(x – 3) – 5(x + 2)(x2 – 2x + 4) = 0
c. x(x + 3)(x – 3) + 5(x – 3) = 0
d. (3x – 1)(x2 + 2) = (3x – 1)(7x – 10)
giải các phương trình sau:
a.(x - 1)(x + 2)= 0
b.(x -2)(x -5)=0
c.(x +3)(x -5)=0
d.(x + 1/2)(4x + 4)=0
e.(x -4)(5x -10)=0
f.(2x -1)(3x +6)=0
g.(2,3x -6,9)(0,1x -2)=0
1,Giải các phương trình sau:
a,(x-4)^2-25 = 0
b,(x-3)^2-(x+1)^2 = 0
c,(x^2-4)(2x-3) = (x^2 - 4 )(x-1)
d,(3x-7)^2 - 4( x+1)^2 = 0
Giải giúp em với ạ :3
Bài 3: Giải các phương trình sau
a. (3x + 2)2 – (3x – 2)2 = 5x + 38
b. 3(x – 2)2 + 9(x – 1) = 3(x2 + x – 3)
c. (x + 3)2 – (x - 3)2 = 6x + 8
d. (x – 1)3 – x(x + 1)2 = 5x (2 – x) – 11(x + 2)
e. (x + 1)(x2 – x + 1) – 2x = x(x – 1)(x + 1)
Bài 3: Giải các phương trình sau:
a, 2x3 - 50x = 0
b, 2x (3x - 5) - (5 - 3x)
c, 9(3x - 2) = x(2 - 3x)
d, (2x - 1)2 - 25 = 0
e, 25x2 - 2 = 0
f, x2 - 25 = 6x - 9
g, 5x(x - 3) - 2x + 6 = 0
h, 3x(x - 7) - 2(x - 7) = 0
i, 7x2 - 28 = 0
j, (2x + 1) + x(2x + 1) = 0
k, (x + 2)2 - (x - 2)(x + 2) = 0
l, x3 + 5x2 - 4x - 20 = 0
m, x2 - 25 + 2(x + 5) = 0
n, x3 - 3x + 2 = 0
o, x2 - 6x + 8 = 0
p, x2 - 5x - 14 = 0
q, (x - 2)2 - (x - 3)(x + 3) = 6
r, (2x - 1)2 - (2x + 5)(2x - 5) = 18
Bài 1: Giải các phương trình sau:
a) 3x – 15 = 0 b) 4x + 20 = 0 c) -5x – 20 = 0 d) 3x + 1 = 7x – 11
e) 3 + 2x = 2(x + 1) g